Checklist of the echinoderm fauna of the Adriatic Sea - Despalatović, Marija; Cvitković, Ivan; Žuljević, Ante (Zootaxa, 2017)
This paper presents a checklist of echinoderm species in the Adriatic Sea. The checklist is based on the review of the available literature data, with temporal coverage from the end of the 18th century to the present day, including the most recent investigations of benthic communities. A total of 108 species have been recorded: 2 species from class Crinoidea, 23 species from class Asteroidea, 22 species from class Ophiuroidea, 22 species from class Echinoidea and 39 species from class Holothuroidea. Non-indigenous echinoderm species have not been observed.